Simple Limbal Epithelial Transplantation (SLET): case reports - Silva, João Pedro Gomes Henn da; Marquezan, Mártin Luís Stival; Stock, Ricardo Alexandre; Bonamigo, Elcio Luiz (O Mundo da Saúde, 2024)
The limbus is a transition zone between the cornea and the conjunctiva of the eye, housing epithelial stem cells responsible for maintaining and ensuring the proper functioning of the cornea. Circumstances that damage these cells lead to a condition known as "limbal stem cell deficiency" (LSCD). Simple Limbal Epithelial Transplantation (SLET) is a technique that involves transferring healthy cells from the limbus of the contralateral eye to the injured corneal region. This study aimed to describe two cases of patients undergoing the SLET technique for limbal insufficiency repair, as well as to evaluate their outcomes with this recent surgical technique. A descriptive, qualitative clinical case report study was conducted through the analysis of medical records of two patients affected by unilateral LSCD. The two patients presented with different etiologies and classifications of the conditions. Case 1 resulted from mechanical trauma, while Case 2 was due to chemical burns. Both underwent the same surgical technique, showing good clinical progression over the follow-up period, with a clear and epithelialized cornea, as well as improved visual acuity and quality of life, without significant complications. In conclusion, the SLET technique demonstrated favorable outcomes in the repair of limbal insufficiency in both cases. However, further studies are required to confirm its potential efficacy and safety in ocular surface reconstruction.